Sharing the American Dream on TikTok: Latin Americans’ social representations of migration - David Ramírez Plascencia; Jezabel Pérez Yañez; Rosa María Alonzo Gónzalez (Cuadernos.info)
Latin American migrants have found a great ally in digital media to organize their ressetlement, access key information, and connect with support networks. Through their daily digital networking, they have built virtual communities to stay in touch with their culture in their home countries. These communities foster the construction of collective visions, meanings and representations about their conditions, context and status as migrants. This article aims to understand how Latin Americans have created social representations (SR) about migration in social media related to the American dream by analyzing the audiovisual discourse in videos created, commented, and shared on TikTok. We found that social interaction between users of this platform creates a collective representation associated with latent promises of prosperity, but also with potential risks, dangers and disappointment about migration to the United States.